The Effect of Job Satisfaction and Work Motivation on Employee Performance in Terminal Operations at Bandung Husein Sastranegara Airport - Jenal Abidin; Nur Makkie Perdana Kusuma (CV. Rayyan Dwi Bharata, 2022)
The performance of an employee is basically an individual thing because each employee has different levels in doing their job duties. This study aims to determine how much influence job satisfaction has on employee performance at the operational center of the Husein Sastranegara Airport terminal in Bandung. To find out how the influence of work motivation on employee performance at the terminal operation center of Husein Sastranegara Airport Bandung and to find out how the influence of motivation and job satisfaction on employee performance at Husein Sastranegara Airport Bandung, especially at the airport terminal operation center. This research uses a type of quantitative research design. This research is an associative research, where this research was conducted to find out the relationship and influence between variables. Where the sample in this study were all employees at the terminal operation center at Husein Sastranegara Airport Bandung as many as 50 employees using purposive sampling technique. The results of this study indicate that simultaneously job satisfaction and work motivation affect employee performance, with a Tcount of job satisfaction of 2.412 with a significant value of 0.020 0.05, meaning that partially job satisfaction variables affect employee performance at Husein Sastranegara Airport Bandung. As well as the value of Tcount work motivation of 3.249 with a significant value of 0.002 0.05, it shows that simultaneously the variable of work motivation influences employee performance at Husein Sastranegara Airport, Bandung. The effect of job satisfaction and work motivation on employee performance at Husein Sastranegara Airport Bandung is 75.3% while the other 24.7% is influenced by other variables.Keywords: Job Satisfaction, Work Motivation, and Employee Performance